2015
DOI: 10.6026/97320630011254
|View full text |Cite
|
Sign up to set email alerts
|

Current status of preimplantation genetic diagnosis in Japan

Abstract: This is a retrospective study aimingto clarify the current status of preimplantation genetic diagnosis (PGD) in Japan. Our data were collected from 12 facilities between September 2004 and September 2012, and entered into a database. A majority of PGD in Japan was performed for balanced structural chromosomal abnormalities in couples with recurrent miscarriage. PGD for monogenic diseases was performed only in two facilities. The average maternal age was 38 years for monogenic diseases and 40 years for chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Meanwhile, preimplantation genetic diagnosis (PGD) for specific genetic disorders or recurrent miscarriages due to parental balanced structural chromosomal abnormalities is only allowed after the approval of the institutional review board at each facility and the board of ethics at the JSOG. Between September 2004 and September 2012, there were 671 cycles of oocyte retrieval with PGD in Japan, from which 65 singleton babies were born (33). For this study, data from 2007 to 2012 were used because the Japanese ART registry database was established as an online registration system from 2007 by the JSOG.…”
Section: Date Source and Study Samplementioning
confidence: 99%
“…Meanwhile, preimplantation genetic diagnosis (PGD) for specific genetic disorders or recurrent miscarriages due to parental balanced structural chromosomal abnormalities is only allowed after the approval of the institutional review board at each facility and the board of ethics at the JSOG. Between September 2004 and September 2012, there were 671 cycles of oocyte retrieval with PGD in Japan, from which 65 singleton babies were born (33). For this study, data from 2007 to 2012 were used because the Japanese ART registry database was established as an online registration system from 2007 by the JSOG.…”
Section: Date Source and Study Samplementioning
confidence: 99%
“…Furthermore, since 2008, the single embryo transfer (SET) policy introduced by the Japan Society of Obstetrics and Gynecology has significantly decreased the multiple pregnancy rate [13]. In addition, BT facilitates preimplantation genetic testing (PGT) [14]. However, there remain concerns about BT and its adverse effects with regard to higher SSR and increased incidence of monozygotic twinning (MZT).…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal diagnosis for mtDNA-related mitochondrial diseases is prevalent in several countries [8][9][10] . Furthermore, preimplantation genetic testing for Leigh syndrome caused by mtDNA mutation has been reported in Japan 21 . However, recent studies indicated that prenatal samples provide an accurate prediction of mtDNA mutation load in the postnatal period 22 .…”
Section: Discussionmentioning
confidence: 99%